2003
DOI: 10.1179/000349803235001697
|View full text |Cite
|
Sign up to set email alerts
|

The co-administration of ivermectin and albendazole - safety, pharmacokinetics and efficacy againstOnchocerca volvulus

Abstract: A randomized, double-blind, placebo-controlled trial was conducted, to determine whether the co-administration of ivermectin with albendazole is safe and more effective against Onchocerca volvulus than ivermectin alone, and whether a significant pharmacokinetic interaction occurs. Forty-two male onchocerciasis patients received ivermectin (200 mug/kg) alone, albendazole (400 mg) alone or the combination. Safety was determined from the results of detailed clinical and laboratory examinations before treatment, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 13 publications
5
61
0
Order By: Relevance
“…However, before two drugs can be recommended for simultaneous treatment, in vitro and in vivo studies are necessary to rule out potential drug interactions. To our knowledge, to date only the coadministration of albendazole plus ivermectin has been thoroughly studied (8,9). The aim of the present work was therefore to assess the combined therapies of albendazole plus oxantel pamoate and albendazole plus mebendazole for potential drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before two drugs can be recommended for simultaneous treatment, in vitro and in vivo studies are necessary to rule out potential drug interactions. To our knowledge, to date only the coadministration of albendazole plus ivermectin has been thoroughly studied (8,9). The aim of the present work was therefore to assess the combined therapies of albendazole plus oxantel pamoate and albendazole plus mebendazole for potential drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…When coadministering multiple drugs, drug-drug interactions should be ruled out. While the combination of albendazole plus ivermectin has been carefully evaluated in preclinical and clinical studies (8,9) albendazole combined with mebendazole or oxantel pamoate…”
mentioning
confidence: 99%
“…Other studies showed that, to control onchocerciasis, the combination of ivermectin with other drugs offers no advantage over ivermectin alone. Thus, in infected patients, the ingestion of ivermectin had no effect on the kinetics of an oral dose of albendazole and there was no additive effect of both drugs against the parasite compared to ivermectin given alone (25,26,27). Albendazole (400 mg) did not modify the kinetic behavior of a single oral ivermectin dose (12 mg) (27).…”
Section: Interactionsmentioning
confidence: 99%
“…Thus, in infected patients, the ingestion of ivermectin had no effect on the kinetics of an oral dose of albendazole and there was no additive effect of both drugs against the parasite compared to ivermectin given alone (25,26,27). Albendazole (400 mg) did not modify the kinetic behavior of a single oral ivermectin dose (12 mg) (27). Also in onchocerciasis patients, the antiparasitary efficacy was similar when administering a single ivermectin dose (150 ÎŒg/kg, on day 1) followed by amorcazine (3 mg/kg twice daily, on days 8, 9 and 10) than when administering ivermectin alone (28).…”
Section: Interactionsmentioning
confidence: 99%
“…91 Although coadministration of albendazole and ivermectin did not seem to enhance the mosquitolethal, sublethal, or sporontocidal effects of ivermectin, it is important to note that it does not inhibit these phenomena. Because albendazole does not alter the systemic exposure of ivermectin, [92][93][94] it is likely that coadministration of these drugs by MDA would produce the same impact on Plasmodium transmission as ivermectin alone but would maximize impact against STHs. To assess whether albendazole coadministered with ivermectin during MDA alters the mosquito-lethal effect of ivermectin MDA, An.…”
Section: Ivermectin and Albendazole Mda Impacts On Malaria Parasite Tmentioning
confidence: 99%